The Influence of Al-Ghazzali's Rationality in Islamic Education - Diny Mahdany; Wahyudi Rifani; Taufik Hidayat; Muhammad Noor; Usman DP (SYAMIL: Journal of Islamic Education, 2025)
This research is motivated by the need to understand the contribution of Al-Ghazzali's thought in Islamic education, particularly regarding the concept of rationality that integrates reason and revelation. Al-Ghazzali's rationality is considered crucial in addressing the challenges of the modernization of Islamic education, which demands a balance between spiritual and intellectual values. The objective of this study is to examine the influence of Al-Ghazzali's rationality on curriculum development, learning methods, and character formation in Islamic education. The method employed is qualitative research with a library research approach, focusing on content analysis of various relevant primary and secondary sources. Data were collected through documentation techniques and literature studies from books, journals, and scientific articles related to Al-Ghazzali's thought and Islamic education. Data analysis was conducted inductively by grouping main themes that illustrate the relationship between Al-Ghazzali's rationality and Islamic educational practices. The findings indicate that Al-Ghazzali's rationality plays a central role in building the foundation of holistic Islamic education, harmonizing reason and revelation. His thought encourages the use of reflective learning methods and an integrative curriculum that combines religious sciences with general knowledge, while also emphasizing character formation based on Islamic values. In conclusion, the application of Al-Ghazzali's rationality enriches modern Islamic education by balancing the intellectual and spiritual aspects of students. Recommendations for further research include conducting empirical studies to test the direct implementation of Al-Ghazzali's thought in contemporary educational contexts and comprehensively evaluating its impact on the quality of education and student character.